Goal choice in preschoolers is influenced by context, cognitive flexibility, and metacognition - Leclercq, Marion; Gimenes, Guillaume; Maintenant, Célia; Clerc, Jérôme (Frontiers in Psychology, 2023)
Introduction Goal choice is one of the first, and most important, steps in self-regulated learning (SRL). It is particularly challenging for young children (before 5–6 years), who tend to rely on available environmental cues, which makes their goals fragile because of the instability and variability of the environment. Therefore, it can be assumed that the conditions under which a task is performed may influence a child’s learning goal choice. Moreover, adapting to constraints involves control capacities provided by executive functions (EF) and metacognition. Methods The main purpose of this study was to determine factors that influence the way preschoolers choose a learning goal during the first step of SRL. We tested whether adding constraints to perform a task may influence the choice of the procedure that a child aims to learn to perform this task. We also examined the role of cognitive flexibility and metacognition in goal selection in the face of these changes, and tested the influence of change over time, comparing participants’ performance at two points in the school year. One hundred 4-year-olds were asked to perform a jigsaw puzzle task under two conditions: predictable vs. unpredictable environmental change. Individual levels of cognitive flexibility and metacognition were also measured. Results The results show that only a predictable change, but not an unpredictable one, leaded children to change their learning goals. Furthermore, when participants were faced with an unpredictable change, metacognition and cognitive flexibility significantly predicted learning goal change. Results are discussed regarding the development of SRL, flexibility, and metacognition. Educational suggestions are proposed. Highlights – The choice of a learning goal by a preschooler is influenced by the conditions of task performance and environmental cues. Facing a predictable change is more disruptive to children before the age of 4.5, and more likely to cause them to change their goal. – A shift is observed, from age 4 and during the school year, from a perceptual to a conceptual level of processing. – Cognitive flexibility and metacognition also determine learning goal choice in preschoolers, but only in front of unpredictable changes.